Satisfaction with pediatric telehealth according to the opinions of children and adolescents during the COVID-19 pandemic: A literature review - Kodjebacheva, Gergana Damianova; Culinski, Taylor; Kawser, Bushra; Amin, Saman (Frontiers in Public Health, 2023)
Objective To review satisfaction with telehealth among children and adolescents based on their own opinions during the COVID-19 pandemic. Methods In the PubMed, CINAHL, PsycINFO, and Embase databases, we searched for peer-reviewed studies in English on satisfaction with telehealth among children and adolescents (rather than parents). Both observational studies and interventions were eligible. The review was categorized as a mini review because it focused on the limited time frame of the COVID-19 pandemic. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Reviewers extracted information from each study and assessed risk of bias. Results A total of 14 studies were eligible. Studies were conducted in Australia, Canada, Italy, Israel, Poland, South Korea, the United Kingdom, and the United States. They focused on a variety of health conditions. Two of the 14 studies were interventions. Participants expressed high satisfaction with video and telephone visits and home telemonitoring while also preferring a combination of in-person visits and telehealth services. Factors associated with higher satisfaction with telehealth included greater distance from the medical center, older age, and lower anxiety when using telehealth. In qualitative studies, preferred telehealth features among participants included: a stable Internet connection and anonymity and privacy during telehealth visits. Conclusion Telehealth services received favorable satisfaction ratings by children and adolescents. Randomized-controlled trials on the effectiveness of pediatric telehealth services compared to non-telehealth services may assess improvements in satisfaction and health outcomes.